2011
DOI: 10.1007/s00415-011-5970-8
|View full text |Cite
|
Sign up to set email alerts
|

Addition of serum-containing medium to cerebrospinal fluid prevents cellular loss over time

Abstract: Immediately after sampling, leukocyte counts in native cerebrospinal fluid (CSF) start to decrease rapidly. As the time lapse between CSF collection to analysis is not routinely registered, the clinical significance of decreasing cell counts in native CSF is not known. Earlier data suggest that addition of serum-containing medium to CSF directly after sampling prevents this rapid decrease in leukocyte counts and, thus, may improve the accuracy of CSF cell counting and cell characterization. Here, we prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 10 publications
3
55
0
Order By: Relevance
“…Conversely some deterioration was seen, even with refrigeration, with samples collected in glass tubes without an anticoagulant 33. For CSFs it has been shown that adding serum could stabilise the cells for 5–24 h,57 58 but this approach is not usually adopted for practical reasons.…”
Section: Sample Stabilitymentioning
confidence: 99%
“…Conversely some deterioration was seen, even with refrigeration, with samples collected in glass tubes without an anticoagulant 33. For CSFs it has been shown that adding serum could stabilise the cells for 5–24 h,57 58 but this approach is not usually adopted for practical reasons.…”
Section: Sample Stabilitymentioning
confidence: 99%
“…Within 30 minutes after sampling, the CSF cell number decreases significantly (9,14,34,(84)(85)(86). Also, differences in survival rate between different leukocyte subsets were observed: monocytes and granulocytes showed a more rapid cell loss than lymphocytes (9,34,85; Table 3).…”
Section: Rapid Decline Of Leukocyte Counts Upon Lumbar Puncturementioning
confidence: 99%
“…In an earlier study, we showed that addition of serum-containing medium (RPMI-1640 with HEPES, L-Glutamine, Penicillin/Streptomycin, heat-inactivated fetal bovine serum, and heparin) preserves CSF cells until at least five hours after sampling (9). Another study showed that immediate addition of Earle's balanced salt solution with human serum albumin to CSF prevents total WBC loss until at least 24 hour after sampling (86).…”
Section: Rapid Decline Of Leukocyte Counts Upon Lumbar Puncturementioning
confidence: 99%
“…This result is consistent with previous studies that used media to preserve cell markers for flow cytometry on CSF specimens. [9][10] Based on these results, we concluded that laboratories such as ours who are not open 24 hours a day, 7 days a week should routinely be adding media to all CSF specimens that cannot be processed immediately. Alternatively, if the cytology laboratory is in a hospital with a hematology laboratory that is open 24 hours, they might consider having the hematology laboratory make the specimen for cytology at the time of receipt.…”
Section: Discussionmentioning
confidence: 88%
“…8 Studies using CSF and flow cytometry have shown significant cell marker loss (30%) in as little as 4 hours, which can be prevented by the addition of media. 9,10 Media is also used routinely in blood storage and preservation. 11 To clarify the possible role of media in the preservation of CSF cytology specimens, we examined the effect that the addition of media to cytology CSF specimens had on the cellularity of specimens processed 24 hours and 48 hours after receipt.…”
Section: Introductionmentioning
confidence: 99%